2019
DOI: 10.21203/rs.2.12869/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small RNA-seq analysis of exosomes from porcine uterine luminal fluid during peri-implantation

Abstract: Background The exosomes of uterine luminal fluid (ULF) mediate intrauterine communication between conceptus and uterus in pigs. The small RNAs of ULF exosomes are widely recognized as important factors that influence embryonic implantation in humans, mice, cattle and sheep. Therefore, it can be hypothesized that small RNAs of ULF exosomes are essential for implantation in pigs. Results Cup-shaped exosomes (diameters: 40–160 nm) of porcine ULF were isolated and characterized, and then PKH67 stained exosomes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…EVs transport a subset of small RNAs during the implantation cascade (Bidarimath et al, 2017;Hu et al, 2022;Hua et al, 2021;Szuszkiewicz, Myszczynski et al, 2022). In line with dynamic molecular changes occurring at the embryo-maternal interface, miRNA cargo composition also changes in uterine-derived EVs after maternal recognition of pregnancy.…”
Section: Implantation Cascade (Days 13−19)mentioning
confidence: 95%
See 3 more Smart Citations
“…EVs transport a subset of small RNAs during the implantation cascade (Bidarimath et al, 2017;Hu et al, 2022;Hua et al, 2021;Szuszkiewicz, Myszczynski et al, 2022). In line with dynamic molecular changes occurring at the embryo-maternal interface, miRNA cargo composition also changes in uterine-derived EVs after maternal recognition of pregnancy.…”
Section: Implantation Cascade (Days 13−19)mentioning
confidence: 95%
“…RNA cargo analysis of porcine uterine-derived EVs at the time of maternal recognition showed enrichment in small biotypes (Hua et al, 2021;Szuszkiewicz, Myszczynski et al, 2022). Bioinformatic analysis of identified specific miRNAs, of possible endometrial and embryonic origin, showed their potential to target genes involved in endometrial receptivity and embryo development by regulating processes such as cell differentiation and cell adhesion, but also processes of embryo-maternal communication-molecular transport and signal exchange between cells (Hu et al, 2022;Hua et al, 2021;Szuszkiewicz, Myszczynski et al, 2022). Other studies showed that the effect of uterine-derived EVs on porcine trophoblast cells depends on their concentration and varies between Days 9 and 12 of pregnancy.…”
Section: Maternal Recognition Of Pregnancy (Days 115−12)mentioning
confidence: 99%
See 2 more Smart Citations
“…EVs have already gained attention among reproductive biologists, providing increasing data on their specific roles (17)(18)(19). To date, EVs have been identified as being released by embryos from the earliest days after fertilization (20)(21)(22), through the periimplantation phase (23)(24)(25)(26)(27), to the stages when placenta is already formed (28). EVs have also been studied in various reproductive pathophysiological conditions and diseases, including preeclampsia (29).…”
Section: Introductionmentioning
confidence: 99%